Antenatal Care among Women in Rural Nepal: A Community-based Study - Sulochana Dhakal; Edwin R van Teijlingen; Jane Stephens; Keshar Bahadur Dhakal; Padam Simkhada; Edwin Amalraj Raja; Glen N. Chapman (Rural Nurse Organization; Binghamton University, 2011)
Background and Objective: The uptake of antenatal care (ANC) is generally poor and inadequate in many developing countries such as Nepal. The purpose of our study was to assess the utilization and associated factors of antenatal care uptake among rural women in Nepal. The study was carried out in two villages and surrounding areas of Kathmandu district in 2006.  Sample and Method: A descriptive, cross-sectional study, which was conducted among 150 women of reproductive age who had delivered a live baby within the 24 months preceding the survey. All women were interviewed using a semi-structured questionnaire. Findings: Women were influenced by their mother-in-laws on whether or not to use ANC. Utilization of ANC was associated with many factors: women having their second or subsequent pregnancy, illiteracy; Tamang ethnicity, women whose husbands were farmers, and women who were farmers themselves (p<0.001). Younger women and those with secondary education were statistically more likely to have used ANC. Twenty-two percent of women did not receive ANC. Services offered during ANC included for most women supply of supplementary iron and folic acid tablets (95%) and checking of maternal weight (94%). Few women reported having received information on danger signs of pregnancy (27%), and 16% women had experienced health problems during their last pregnancy.  Conclusion: The utilization of ANC (at least one visit in pregnancy) in our rural study was encouraging as it was higher than the national average, and even fewer women manage to get four ANC visits as recommended by the World Health Organization. The accessibility of ANC programs that incorporate an awareness-raising element to encourage pregnant women to attend may help improve ANC uptake. Keywords: Utilization, Antenatal care, Prepartum Care, Rural Women, South Asia